Hierarchical Self‐Assembly of Peptides and its Applications in Bionanotechnology. Issue 14 (25th April 2019) - Gerbelli, Barbara B.; Vassiliades, Sandra V.; Rojas, Jose E. U.; Pelin, Juliane N. B. D.; Mancini, Rodrigo S. N.; Pereira, Wallace S. G.; Aguilar, Andrea M.; Venanzi, Mariano; Cavalieri, Francesca; Giuntini, Francesca; Alves, Wendel A.
Abstract: Self‐assembled structures obtained from organic molecules have shown great potential for applications in a wide range of domains. In this context, short peptides prove to be a particularly versatile class of organic building blocks for self‐assembled materials. These species afford the biocompatibility and polymorphic richness typical of proteins while allowing synthetic availability and robustness typical of smaller molecules. At the nano‐to‐mesoscale, the architectures obtained from peptide units exhibit stability and a large variety of morphologies, the most common of which are nanotubes, nanoribbons, and nanowires. This review describes the formation of peptide‐based self‐assembled structures triggered by different stimuli (e.g., ionic strength, pH, and polarity), and the interactions that drive the assembling processes. It is surveyed how judicious molecular design is exploited to impart favourable assembling properties to afford systems with desired characteristics. A large body of literature provides the experimental and in silico data to predict self‐assembly in a given peptide system and obtain different supramolecular organizations for applications in a wide range of fields, from transport to sensing, from catalysis to drug delivery and tissue regeneration. Abstract : The self‐assembly properties of peptide nanomaterials in relation to their design and composition are surveyed in this review. It emphasizes how the morphology of peptide nanostructures can be influenced by environmental conditions, and how this dependence can be suitably exploited for the design of stimuli‐responsive systems.